How to visit an art museum tips for a truly rewarding visit - Idema, Johan (BIS Publishers, 2014)
The only way to understand art is to go to a museum and look at it, French painter Renoir suggests. But once inside, this is easier said than done. What do you do when the label simply reads "Untitled, 1973"? Where to look when a painting offers you a picturesque but undisguised view of a giant vagina? And how to react, when the museum guard stares at you for far too long? 'How to Visit an Art Museum' offers fresh perspectives on how to behave once inside the museum. Whether first-timer or frequent visitor, it shows you the sense and nonsense of museum etiquette. The typical museum behavior - "Walk slowly, but keep walking" - is seldom the most rewarding. That's why this book encourages you to look outside the box and tackle the challenges that art presents to us by taking things into your own hands. Find out how you can use museum guards to your advantage. Learn the rules of thumb to distinguish good from bad art. Explore how kids are able to offer you glimpses of the world that's hidden behind an artwork. How to Visit an Art Museum shows you how a little courage and creativity can go a long way to making your museum visit truly worthwhile. Because ultimately, the art museum is what you make it. 'How to Visit an Art Museum' is an accesible, fun and rewarding read. It's a book full of tips and inspiring illustrations, but also written with a serious undertone. Because it does make sense to stop wandering and start acting the next time you visit an art museum. You will be surprised how much more rewarding your visit will be